Advancing cancer therapy: the role of silver(I) phosphine complexes in overcoming resistance and toxicity - Reinout Meijboom; Austine Ofondu Chinomso Iroegbu; Suprakas Sinha Ray (Discover Oncology)
Abstract Silver(I) phosphine complexes have attracted significant attention recently due to their structural versatility and promising anticancer properties. These complexes exhibit diverse coordination geometries—ranging from tetrahedral and trigonal planar to linear—depending on the ligand environment and metal-to-ligand ratio, directly influencing their biological activity. Notably, they demonstrate substantial cytotoxicity against various cancer cell lines, including oesophageal (SNO), breast (MCF-7), and lung (A549) cancers, with IC₅₀ values in the low micromolar range. A key advantage of these complexes is their selective toxicity toward malignant cells while sparing healthy ones, positioning them as potential alternatives to traditional chemotherapeutics like cisplatin, often associated with severe side effects and drug resistance. The anticancer mechanism of silver(I) phosphine complexes primarily involves apoptosis induction through mitochondrial disruption, phosphatidylserine externalisation, and caspase activation. Additionally, these complexes can overcome common resistance mechanisms encountered in conventional cancer treatments by targeting alternative cellular pathways. This review critically evaluates the structural chemistry, synthesis, and characterisation of silver(I) phosphine complexes and recent advancements in their biological applications. Furthermore, we discuss their potential to address critical limitations in cancer therapies, particularly in overcoming drug resistance and toxicity, while exploring opportunities for ligand optimisation and progress toward clinical applications.